K88-mediated binding of Escherichia coli outer membrane fragments to porcine intestinal epithelial cell brush borders. - Middeldorp, J M (1981)
We have examined the interactions between various radiolabeled membrane fractions obtained from an enterotoxigenic Escherichia coli strain and brush borders isolated from porcine intestinal epithelial cells. Outer membrane fragments containing the K88 attachment factor bound tightly to brush borders, whereas cytoplasmic membrane vesicles did not. Three different types of outer membrane preparations were tested: (i) cellular outer membranes isolated from lysozyme spheroplasts, (ii) medium vesicles or outer membrane fragments released into the medium during growth, and (iii) periplasmic vesicles, or outer membrane fragments which were released from the cells during spheroplast formation and were therefore isolated in the periplasmic fraction. Of these fractions, which were heterogeneous, it was always the outer membrane subfraction which bound tightly to brush borders. This binding, which was K88 dependent, may have some physiological significance in view of the association between outer membrane fragments and enterotoxin. Thus, released outer membrane fragments equipped with attachment factors may function as enterotoxin carriers which increase the efficiency with which enterotoxin can be delivered to intestinal epithelial cells.